Safety performance functions for road control sections in Costa Rica - Hernández Vega, Henry (2025)
Road crashes represent a high social and economic cost for the country. For this reason, the Costa Rican National Road Network is studied to determine those control sections with potential for improvement using road safety performance functions.The study is performed by applying the method of expected excess frequency of crashes, adjusted with empirical Bayes. The methodology is taken from the AASHTO Highway Safety Manual. The analysis is applied to all control sections with availability of data required for the research, so 911 control sections of the National Road Network are studied.The analyses were performed for four crash models: total crashes, minor injuries only, fatalities or serious injuries only, and collisions with motorcycles. The control sections with excess frequency of expected crashes were determined. In addition, from the studies performed, it was determined that the number of crashes is mainly influenced by three variables: type of surface, sign condition, and surface width. It is advisable to generate plans to improve road safety in the control sections with the highest excess frequency of expected crashes, since they represent a greater potential for improvement in terms of road safety. On the other hand, it is recommended to study the control sections with lower excess frequency of expected crashes, in order to know the conditions that prevail at these sites.